TECHNIQUES, METHODS, AND IDEOLOGIES OF THE TRANSLATION OF THE WASHFÄª PHRASE NOVEL BANÄ€T AL-RIYÄ€DH IN ENGLISH TO THE QUALITY OF THE TRANSLATION - Jannah, Siti Roudlotul; Yoyo, Yoyo (-)
This research aims to 1) define the washfÄ« phrase in the translated Arabic novel of Girls of Riyadh by Marilyn Booth, 2) describe the technique, method, and quality of translation, 3) to define the ideology of the washfÄ« phrase. This research used the descriptive qualitative method. The respondents evaluated the accuracy, acceptability, and readability of the translation result. This research data resourced with formal and material objects. The material object consists of two Arabic and English version novels. The formal object consists of the washfÄ« phrase of both the novels at once questionnaire. The result of this research there are two kinds of techniques, they are: 1) single variant technique, 2) couplet variant technique. They are 11 techniques: 1) literal 3, 2) established equivalent 3, 3) reduction 1, 4) deletion 3, 5) borrowing 1, 6) generalization 1, 7) particularization 2, 8) variation 4, 9) adaptation 1, 10) addition 1, 11) discursive creation 2, 12) linguistic compression 1, 13) modulation 2. Couplet variant techniques are: 1) deletion+literal 1, 2) modulation+addition 1, 3) modulation+literal 1, 4) particularization + borrowing 1, 5) linguistic compression + particularization 2. This washfÄ« phrase translation has high accuracy levels score 3, high acceptability 2, and low legibility levels 1.